Assessing the Possible Antipoverty Effects of Recent Rises in Age-Specific Minimum Wages in New Zealand - Tim Maloney; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2011)
Real minimum wages increased by nearly 33% for adults and 123% for teenagers in New Zealand between 1999 and 2008. Where fewer than 2% of workers were being paid a minimum wage at the outset of this sample period, now more than 8% of adult workers and 60% of teenage workers are receiving hourly earnings close to the minimum wage. These policy changes provide a unique opportunity to estimate the effects of the minimum wage on the characteristics of these workers and their location across the income distribution. We provide some evidence on the likely consequences of these rising minimum wages on the poverty rate in New Zealand. Although minimum wage workers are more likely to live in the poorest households, they are relatively widely dispersed throughout the income distribution. This is particularly true of teenage minimum wage workers. Furthermore, low-income households often do not contain any working members. We estimate that a 10% increase in minimum wages, even without any offsetting reduction in earnings due to a loss in employment or hours of work, would lower the relative poverty rate by less than one-tenth of a percentage point.
Keywords: I38; J38; J88; 330; New Zealand; Minimum Wage; Poverty